2009
DOI: 10.1532/hsf98.20081068
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minimally Invasive Direct Coronary Artery Bypass and Off-Pump Coronary Artery Bypass in Single-Vessel Disease

Abstract: Although MIDCAB grafting is a challenging technique, it may be safely performed on selected patients with low postoperative mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…Of the RCTs and prospective trials we excluded 9 studies: 6 studies that were retrospective analyses; 2 studies that had no comparator group; and 1 study that had no reported outcomes (see supplementary Figure S1). Eight studies (9 intervention groups) were included in our analysis [5,[8][9][10][11][12][13][14].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the RCTs and prospective trials we excluded 9 studies: 6 studies that were retrospective analyses; 2 studies that had no comparator group; and 1 study that had no reported outcomes (see supplementary Figure S1). Eight studies (9 intervention groups) were included in our analysis [5,[8][9][10][11][12][13][14].…”
Section: Search Resultsmentioning
confidence: 99%
“…The 8 studies (9 intervention groups) [5,[8][9][10][11][12][13][14] included in the analyses had an aggregate of conventional cardiac surgery via a median sternotomy. Table 1 summarizes the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MIDCAB surgery has been gradually accepted by most cardiac surgeons throughout the world [1215]. MIDCAB treatment of LAD lesions with LIMA has a good long-term patency compared with bare stents and vein grafts [16], does not increase the mortality rate or the incidence of myocardial infarction, and the revascularization rate of the MID group was lower than in the PCI group [17].…”
Section: Discussionmentioning
confidence: 99%
“…Coronary bypass surgery can be performed less invasively by avoiding cardiopulmonary bypass (CPB) and sternotomy as beating heart bypass surgery performed through a minithoracotomy with safe and good postoperative results but patient selection is a crucial criteria for this technically challenging operation [2]. As reported in recent studies hig risk patients with severe stenosis of the LAD appear to benefit from ITA grafting in form of the MIDCAB procedure and as in this case combined with a hybrid approach of a two step revascularization together with following angioplasty [3].…”
Section: Discussionmentioning
confidence: 99%